Hubungan Antara Lingkungan Pergaulan Dengan Sikap Dan Perilaku Seks Bebas Remaja Di SMK Murni 2 Surakarta - Rosady Febrianing Tias, Arista, Dwi Astuti, SKM., M.Kes, Tri Puji Kurniawan, SKM, M. Kes (2015)
Free sex is inclined to do by adults. 63% of Indonesian adults ever doing free sex, and 21,2% have had an abortion. Indonesian adults awareness of free sex is measly. Their family still assume that everything which have relation with sex is taboo in their live and the counseling from the government or the school is still measly. Whereas the adults associating environtment is cannot controled well again. The purpose of the research is to knows about the relation between associating environtment which involve: school, family and the society with adults figure and free sex behavior in SMK Murni 2 Surakarta. The kind of this research is an observational research with cross sectional approach. The sample was taken by using the sistematic random sampling method, and got 68 respondent. The data was analyzed by using SPSS which using the test of chi square relationship with 95% significance level. The results of the research shows the relations between the family associating environtment (p=0,008), social associating environtment (p=0,001), and adults free sex figure, the school associating environtment (p=0,014) with adults free sex figure and there are no relations between family associating environtment (p=0,023), school associating environtment (p=0,014), and there are no relations with the family associating (p=0,055), with adults free sex behavior.